Healthy community‐living older men differ from women in associations between myostatin levels and skeletal muscle mass - Li‐Ning Peng; Wei‐Ju Lee; Li‐Kuo Liu; Ming‐Hsien Lin; Liang‐Kung Chen (Wiley, 2018)
Abstract Background Myostatin is a negative regulator of muscle growth but the relationship between serum myostatin levels and muscle mass is unclear. This study investigated the association between serum myostatin levels and skeletal muscle mass among healthy older community residents in Taiwan, to evaluate the potential of serum myostatin as a biomarker for diagnosing sarcopenia and/or evaluating the effect of its treatment. Methods Study data were excerpted from a random subsample of the I‐Lan Longitudinal Aging Study population. Serum myostatin levels were determined and categorized into tertiles (low, medium, high). Relative appendicular skeletal muscle mass (RASM) was calculated as appendicular lean body mass by dual‐energy X‐ray absorptiometry divided by height squared (kg/m2). Low muscle mass was defined as recommended by the Asian Working Group for Sarcopenia. Results The analytic study sample comprised 463 adults (mean age: 69.1 years; 49.5% men). Compared with subjects with normal RASM, those with lower RASM were older and frailer, with significantly higher prevalence of malnutrition, lower serum dehydroepiandrosterone (DHEA) levels, and were more likely to have low serum myostatin status. Multivariable logistic regression analysis showed that male sex (OR 3.60, 95% CI 1.30-9.92), malnutrition (OR 4.39, 95% CI 1.56-12.36), DHEA (OR 0.99, 95% CI 0.99-1.00), and low myostatin (OR 3.23, 95% CI 1.49-7.01) were all independent risk factors for low RASM (all P < 0.05). In men, DHEA (OR 0.99, 95% CI 0.98-1.00) and low myostatin (OR 4.89, 95% CI 1.79-13.37) were significantly associated with low RASM (both P < 0.05); however, only malnutrition was associated with low RASM in women (OR 13.59, 95% CI 2.22-83.25, P < 0.05). Conclusions Among healthy community‐living older adults, low serum myostatin levels were associated with low skeletal muscle mass in men, but not in women. Our results do not support using serum myostatin levels to diagnose sarcopenia, or to monitor how it responds to treatments. Further research is needed to understand why men apparently differ from women in the interrelationship between their myostatin levels and muscle mass.